Enhancement of ultrasonic sensor system for indoor mobile robot mapping and self-localization - Bukhari Ilias (School of Mechatronic Engineering, 2017)
The aim of this research is to develop a mapping and self-localization system using ultrasonic sensor for an appropriate indoor mobile robot. This thesis is concerned with the accuracy issues for a practical differential drive robot for mapping and self-localization applications for easier maneuvering and avoiding obstacle in small and medium scale indoor environments. The principal objectives of this thesis are as follows to develop an enhanced algorithm for suppressing phantom error in mapping; to modify kinematic algorithm for generating a 2D mapping of basic wall shape and real indoor environment; to evaluate the performance of the developed algorithm and the accompanying robot in mapping and self - localization of basic wall shape and real indoor environment.